Characteristics, use patterns and perceptions of electronic cigarette users who were never traditional cigarette smokers. (February 2017) - Hammett, Erin; Veldheer, Susan; Yingst, Jessica; Hrabovsky, Shari; Foulds, Jonathan
Highlights: Less than 2% of adult e-cigarette users were never cigarette smokers. 63% of e-cig users who were never cigarette smokers had used other tobacco products. Studies of e-cig use should collect a full tobacco use history. Never cigarette smokers may use e-cigs to reduce other tobacco product use.